Atomic configuration of hydrogenated and clean tantalum(111) surfaces : bond relaxation, energy entrapment and electron polarization - Bo, Maolin (2020)
By studying the tantalum (Ta)(111) surface with X-ray photoemission spectroscopy and density functional theory, we determined binding energy values for the clean Ta(111) (+3.068 eV) and hydrogenated Ta(111) (+3.421 eV) surfaces with an isolated atom level of 18.977 eV. Using the bond–band barrier and zone-selective electron spectroscopy correlation, we investigated the mechanism of hydrogenation adsorption on the Ta(111) surface. We found the local densities of states of the first layer of Ta atoms in the reconstructed structure, which formed on the adsorbent hydrogen of the surface chemical bond contracts and dipole polarization. Moreover, we showed that on the Ta(111) surface, the hydrogen-induced surface core level shifts are dominated by quantum entrapment and are proportional to the calculated hybridized orbitals of the valence band. The latter is therefore correlated to the local surface chemical reactivity and is useful for other adsorbate systems on transition metals.